Self-Guided Web-Based Pain Education for People With Musculoskeletal Pain: A Systematic Review and Meta-Analysis. Issue 10 (25th June 2021) - de Oliveira Lima, Lívia; Saragiotto, Bruno T; Costa, Leonardo Oliveira Pena; Nogueira, Leandro Calazans; Meziat-Filho, Ney; Reis, Felipe J J
Abstract: Objective: The purpose of this study was to investigate the effectiveness of web-based pain education programs without clinical support in patients with musculoskeletal pain. Methods: PubMed, Scopus, CINAHL, Web of Science, Cochrane Library, and PsycINFO were searched from inception to February 2020. Included studies were randomized clinical trials in which people with musculoskeletal pain were allocated to an experimental group that received web-based pain education as a standalone approach. Three review authors performed data extraction. The PEDro (Physiotherapy Evidence Database) scale was used to assess the methodological quality of the studies. The primary outcomes were pain intensity and disability. Results: Six trials with a total of 1664 participants were included. There is moderate-quality evidence with a small effect size that web-based pain education programs, as a standalone approach, are better than minimal intervention (no intervention or booklets) for pain intensity (standardized mean difference [SMD] = −0.23; 95% CI = −0.43 to −0.04) in the short term and intermediate term (SMD = −0.26; 95% CI = −0.42 to −0.10). Regarding disability, there is low-quality evidence that web-based pain education programs are better than minimal intervention (SMD = −0.36; 95% CI = −0.64 to −0.07) in the short term. Web-based pain education added to usual care was no better than usual care alone in the intermediate or long term for primary outcomes. Conclusions: Web-based pain education for adults with musculoskeletal pain, as a standalone approach, was better than minimal intervention for pain intensity and disability in the short term, and for pain intensity in the intermediate term. Web-based pain education added to usual care did not provide additional benefits for primary outcomes in the intermediate or long term. Impact: Web-based pain education as a standalone intervention provided small improvements in pain intensity and disability in patients with chronic musculoskeletal pain. Poorly resourced settings and overburdened health systems should consider this delivery method in the management of chronic musculoskeletal pain. Lay Summary: If you have chronic musculoskeletal pain, your physical therapist might recommend web-based pain education as treatment to help you reduce pain intensity and disability.